Exploring job satisfaction and workplace engagement in millennial nurses - Waltz, Lee Ann; Muñoz, Laura; Weber Johnson, Holly; Rodriguez, Tracy (Journal of nursing management, 2020)
Aim To examine job satisfaction and workplace engagement of millennial nurses. Background Millennial nurses are a rapidly growing segment of the workforce. They are significantly less satisfied in their jobs compared with nurses of other generations and are more likely to have perceptions that may negatively impact job satisfaction and engagement. It is important for nurse leaders to understand and value the perspective of these nurses to improve job satisfaction and engagement. Method Exploratory‐descriptive qualitative approach with 33 millennial nurses interviewed in nine focus groups. Results Five themes revealed areas that both enhance and hinder job satisfaction and engagement. Themes include the following: (1) professional relationships; (2) rewards; (3) communication; (4) professional development; and (5) workload/staffing. Conclusion Concerns identified by millennial nurses provide direction for nurse leaders who are charged with fostering a workplace setting that nurtures empathy and respect for nurses of all generations. Implications for Nursing Management Strategies to address preferences of millennials include employee rounding to ask about their needs, offer assistance and provide positive feedback. Ongoing mentoring regarding opportunities to support millennials’ professional development includes offering participation in activities to advance evidence‐based practice, preceptor training, financial assistance with national certification examinations and tuition reimbursement.